The study on milling machining for aluminium alloy - Goh, H.W (University Malaysia Sarawak, (UNIMAS), 2004)
This research investigates the effect of the spindle speed, feed rate and depth of cut on surface finish of aluminium alloy. The experiment is done by carrying out several milling operation based on above parameters using CNC milling machine.